Promoting Community‐Led Monitoring of Taonga (Treasured) Species and Freshwater Health Through eDNA Metabarcoding - Amy A. Gault; Susan A. Welsh; Arapera Paewai; Penelope Drysdale; Shaun P. Wilkinson; Hone Morris; Erana Mōtū; Hineatatu Dorset; Rose Collis; Adrian Cookson (Environmental DNA)
ABSTRACT In response to intensified agricultural impacts on Aotearoa New Zealand's river systems, our study sought to demonstrate a novel approach for assessing freshwater quality through environmental DNA (eDNA) and promote a holistic understanding of ecological health. Employing 13 eDNA tree‐of‐life metabarcoding assays alongside 11 standard physicochemical attributes, we generated a comprehensive temporal and spatial dataset along a 3.5 km section of an upper river catchment. The study catchment moves from a culturally significant native bush area, through sheep and beef farming, to an organic dairy farm, capturing the transition through varying land uses. Our analysis focused on the detections of key culturally significant taonga (treasured) species, known animal sources of fecal contamination, and the taxon‐independent community index (TICI) as a measure of ecological health. We identified 479 species including whīo/native blue duck, long and short finned tuna/eels, kaharore bully/cockabully, kōkopu/dwarf galaxias, and kōura/freshwater crayfish. Although Escherichia coli (E. coli) levels did not significantly vary across sites, eDNA sequence counts of cattle and deer were significant predictors of a site's E. coli levels, suggesting that eDNA could be a valuable indicator of fecal contamination sources. TICI scores were strongly correlated with changes in water quality attributes (Adj‐R2 = 0.92) and consistently detected subtle declines driven by increased pastoral land use. Community leadership was central to our methodology, enabling local stakeholders, including mana whenua and farmers, to actively participate in water monitoring and data interpretation. This approach not only fulfilled regulatory requirements but also fostered a deep connection with the river, enhancing community‐led conservation efforts. By enhancing the mauri (life force) of the community through active participation and capacity building, this approach exemplifies sustainable, collaborative efforts in environmental management and revitalization.